Methodology for Generating a Reference Wind Year for Offshore Wind Energy: A Case Study in La Guajira, Colombia - Ospino-Castro, Adalberto; Navas, Sharys Romero; Robles-Algarín, Carlos (International Journal of Energy Economics and Policy, 2024)
Due to its excellent potential, wind power has gained importance as a renewable energy source in Colombia, especially in the offshore Caribbean region. However, one of the main challenges in the development of offshore wind projects is the analysis of the wind resource. This study presents the generation of a specific typical meteorological year (TMY) for wind energy in the Colombian Caribbean region, known in the literature as Reference Wind Year (RWY). The methodology used was based on the Sandia method, widely accepted in the analysis of wind resources. A comparison between the cumulative distribution function (CDF) and the statistic approach Finkelstein-Schafer (FS) was applied to evaluate multiple meteorological parameters in the study area associated with wind resource potential assessment, such as wind speed and direction, temperature and atmospheric pressure, compiled for 10 years (2012-2021). The representative years were weighted according to their importance and combined into a dataset. The results indicated that the proposed method was able to generate highly representative and accurate data for the case study in La Guajira, Colombia, guaranteeing its suitability for implementation in other locations with different climatic conditions.